Artificial Intelligence: ethical and social considerations (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Embedding ethical principles in the development of any technology is becoming more paramount as new questions arise on security, accountability, fairness and more. In this paper, we explained why the case for AI is different and call for better principles and thoughtful design. We then outline a set of recommendations that stem from a definition of rights resulting from principles and ethical values, and conclude with some brief discussion on biases and technical frameworks.
Keywords: AI Knowledge Map; Bias; AI Principles; Data Ownership; Explainability